Developing an exercise program to improve the biomotor abilities of Wushu Taolu athletes as a support for the Teng Kong Bai Lian (TKBL) movement - lituhayu, Kamilia; Nasrulloh, Ahmad; Yuniana, Rina; Omar Dev, Roxana Dev (Universitas Negeri Yogyakarta, 2023)
The aim of this study was: (1) to develop an appropriate circuit training program for biomotor improvement that supports Teng Kong Bai Lian (TKBL), (2) to examine the feasibility of biomotor improvement that supports TKBL, and (3) to examine training program effectivity. This study is a kind of Research and Development through several procedures, such as observation and data collection, planning, program development, expert validation, initial program revision, small scale trial, large scale trial, operational program revision, effectivity test, and completion program, and training program implementation. Instrument of this study consist of observation, questionnaire for expert validation, test and measurement biomotor including (1) t-test for measuring speed and agility, (2) leg dynamometer for leg strength, (3) vertical jump for leg power, (4) curl-up test for core strength, (5) modified bass test of dynamic balance for measuring dynamic balance. The results of the collected data will be analyzed using Aiken for expert validation, and small and large-scale trials, while the paired sample t-test with SPSS is used to analyze the effectiveness test. Expert validation, small-scale trial, and large-scale trial were analyzed using the Aiken method with Aiken table value, whereas the effectivity test was analyzed using paired sample t-test on the SPSS application. The result showed that expert validation for the training program was obtained above 0.80 Aiken value for all test items. The results of the effectiveness test showed a significant effect on increasing the biomotor component of leg muscle strength, core strength, leg muscle explosive power, speed and agility with a P value of 0.000, but the effect was not significant on the balance component where the P value was 0.840. Based on the results of the study, it can be concluded that the ciccuit training program can effectively increase leg muscle strength, core strength, leg muscle explosive power, speed and agility, but does not improve balance. So this training program can be applied to Wushu Taolu athletes to improve their biomotor abilities to support the TKBL movement.Keywords: Wushu, circuit training program, strength, core strength, power, speed, agility, balance